Effects of nanocapsules containing lumefantrine and artemether in an experimental model of cerebral malaria - Bianca Portugal Tavares de Moraes; Karoline Paiva da Silva; Karina Paese; Adilson Paulo Sinhorin; Silvia S. Guterres; Adriana R. Pohlmann; Isabelle Moraes-de-Souza; Sarah de Oliveira Rodrigues; Kauê Francisco Corrêa e SouzaSouza; Carolina Medina Coeli da Cunha; Matheus Augusto Patrício de Almeida; Patrícia Torres Bozza; et al. (Discover Nano)
Abstract Background Malaria, a tropical neglected disease, imposes a significant burden on global health, leading to the loss of thousands of lives annually. Its gold standard treatment is a combination therapy of lumefantrine (LUM) and artemether (ART). Nanotechnology holds significant potential for improving drug bioavailability and potency while reducing adverse effects. Objectives This study aimed to develop lipid-core nanocapsules containing ART and LUM and evaluate their effects in an experimental cerebral malaria model (ECM). Methods The polymeric interfacial deposition method was used to develop lipid-core nanocapsules (LNCs) containing ART and LUM (LNCARTLUM) and were characterized using micrometric and nanometric scales. Male C57BL/6 mice were infected with Plasmodium (P.) berghei ANKA (PbA, 1 × 105 PbA-parasitized red blood cells, intraperitoneally). On day 5 post-infection, PbA-infected mice were orally administered with ART + LUM, LNCARTLUM, blank nanocapsules (LNCBL), or ethanol as a control. Parasitemia, clinical scores, and survival rates were monitored throughout the experiment. Organ-to-body weight ratios, cytokine quantification, and intravital microscopy analyses were conducted on day 7 post-infection. Results LNCs were successfully developed and characterized. The treatment with LNCARTLUM in ECM resulted in complete clearance of parasitemia at 10 dpi, decreased clinical scores, and maintained 100% survival rates. Thereated mice exhibited splenomegaly and reduced TNF-α, IL-1β, and MCP1 levels in the brain. Furthermore, the LNCARTLUM treatment protected the brain microvasculature, reducing the number of cells in the rolling process and adherent to the microvasculature endothelium. Conclusion Nanoformulations can potentially improve the efficacy of antimalarial drugs and be considered a promising approach to treat malaria.